Associação da altura do pasto e níveis de suplementação para bovinos de corte no período de transição águas-seca - Mousquer, Claudio Jonasson (2015)
The beef cattle production in Brazil has been challenged to get production systems to be able to produce efficiently quality meat with reduced prices. When the grazing is well managed, it has a lower cost of feed for the meat production. When it is effective becomes responsible for the biggest economic and productive impact within the production systems adopted in Brazil for the development and production of beef cattle. The use of supplementation in pasture to bovine’s system provides diets with adequate levels of protein and fiber, improving the production indexes and promoting a reduction in the permanence of the animals in the pasture. It favors the precocity and finishing cattle. The use of multiple supplements in dry-water transition period is essential to maintain the growth curve of cattle and slaughter young animals basically fed with tropical forages. The animals’ supplementation fed with low-quality forage is the opportunity to remedy the existing deficit between the nutrients supplied by the forage and the demand of the animals. However, if the forage is the main source of nutrients in the system, it is important that the supplementation do not promote negative impact on the consumption of nutrients that can be harvested by animals in grazing. Therefore the use of supplementation strategy depends on the producer's objectives tied to the cost benefit of this practice. This study aimed to emphasize the use of supplementation (0.1, 0.3 and/or 0.6% of BW) of beef cattle on pasture system at different times (25 and 35 cm) in dry-water transition period and, its implications in animals parameters seeking to maximize the system and demonstrating the strategies for positive responses of using some supplementation during the dry-water transition period.